Perception of the beauty and body image in Czech Republic, Slovakia and Hungary with application on beauty industry - Chotváč, Richard (2013)
ABSTRACT CHOTVÁČ, Richard: Perception of beauty and body image in Czech Republic, Slovakia and Hungary and its application in beauty industry. [Master thesis] -- University of Economics in Prague, VŠE. Faculty of Business Administration; Tutor: doc. Ing. Jan Koudelka, CSc. Prague: VŠE, 2013, 82pages. The Master thesis deals with the perception of the beauty in 3 countries, Czech Republic, Slovakia and Hungary. This thesis is showing differences between the perception of body image and beauty of women in 3 different countries by looking at the consumer's behavior. The first part of the thesis is theoretical and it is devoted to the definitions of beauty and body image of women. The Author shows consumers' differences between studied countries and the consequences of these differences. The objective of the second part is to analyze the survey of multiple respondents from Czech Republic, Slovakia and Hungary. Results of this survey are used in order to demonstrate differences in women's perception of the beauty shown in the theoretical part. Last part shows the practical approach to the thesis. Based on results from the survey, the author proposes the recommendations to the beauty industry marketers working for these countries. Key words: , , , , , , ,